Pedogenesis of soils formed on jurassic calcareous sedimentary rock formations: A transect study in northern semi-arid highlands of Ethiopia - Kahsay, Araya; Haile, Mitiku; Gebresamuel, Girmay; Mohammed, Muktar (Geoderma Regional, 2023)
With the objective of examining soil characteristics, pedogenic processes and classification in association to local environmental and landscape attributes, a transect study was carried out in Hnitalo Wajerat district of Northern Ethiopia. Six pedons beded on shale and dolerite parent rocks were investigated. The soils were sandy loam to clay in texture, moderately porous, neutral to strongly alkaline, nonsaline, base-rich and calcareous. The dominant pedogenic processes prominent in soils of the area were calcification, vertization, argilluviation, melanization and colloidal eluviations. Mollic and ochric horizons were noticed on surface horizons, while cambic, calcic and vertic horizons were found to be the dominant subsurface horizons. Steep upslope areas were characterized by shallow gravelly soils with continuous hard rock. Shrink-swell cracks, colluvic materials and deep soils were prominent on flat areas. The soils of the area were classified as Leptosols/Entisols, Cambisols/Inceptisols, Calcisols/Aridisols and Vertisols. The study evidenced that the pedogenic processes and soil development were largely patterned by terrain positions, lithology and land use type.